Are U.S. Presidents Becoming Less Rhetorically Complex? Evaluating the Integrative Complexity of Joe Biden and Donald Trump in Historical Context. (October 2022) - Conway, Lucian G.; Zubrod, Alivia
Are U.S. political leaders becoming simpler in their rhetoric? To evaluate, we place the two most recent Presidents' integrative complexity against a historical context for three different types of comparable materials. Results reveal that both Biden and Trump are simple when compared to the typical President. Further, segmented regression analyses reveal Biden's and Trump's low complexity is partially the continuation of an ongoing historical decline in complexity among Presidents. Importantly, this complexity decline is occurring for both Republicans and Democrats.